Raised serum bile acid concentrations after occupational exposure to styrene: a possible sign of hepatotoxicity?. Issue 2 (May 1984) - Edling, C; Tagesson, C
Abstract : Fasting serum concentrations of conjugated bile acids were investigated in 23 men who had been exposed to styrene and compared with the concentrations in 60 non-exposed individuals. Eleven of the exposed subjects had raised concentrations of either cholic acid or chenodeoxycholic acid or both. There were no indications of alcohol abuse, drug intake, or undiagnosed liver disease. It is possible, therefore, that the raised bile acid concentrations were due to exposure to styrene. This would support the concept that occupational exposure to styrene may affect the liver and point to the possibility that raised serum bile acid concentrations might be a sensitive and early indicator of hepatic injury in individuals exposed to organic solvents.